2021
DOI: 10.1038/s41598-021-81819-y
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Müllerian hormone (AMH) autocrine signaling promotes survival and proliferation of ovarian cancer cells

Abstract: In ovarian carcinoma, anti-Müllerian hormone (AMH) type II receptor (AMHRII) and the AMH/AMHRII signaling pathway are potential therapeutic targets. Here, AMH dose-dependent effect on signaling and proliferation was analyzed in four ovarian cancer cell lines, including sex cord stromal/granulosa cell tumors and high grade serous adenocarcinomas (COV434-AMHRII, SKOV3-AMHRII, OVCAR8 and KGN). As previously shown, incubation with exogenous AMH at concentrations above the physiological range (12.5–25 nM) decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…No direct effect of lead on this signaling pathway has been demonstrated [16]. -Anti-Müllerian hormone (AMH) at physiological concentrations promotes the proliferation and survival of ovarian cancer cells; again, no direct effect of lead on this signaling pathway has been demonstrated [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…No direct effect of lead on this signaling pathway has been demonstrated [16]. -Anti-Müllerian hormone (AMH) at physiological concentrations promotes the proliferation and survival of ovarian cancer cells; again, no direct effect of lead on this signaling pathway has been demonstrated [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 1000 patients, the overall risk of prostate cancer has been demonstrated to be correlated with prediagnostic serum AMH levels [29]. Physiological concentrations of endogenous AMH increased the viability of cancer cells [30]. Furthermore, serum amyloid A1 (SAA1) is an inflammatory high-density lipoprotein.…”
Section: Discussionmentioning
confidence: 99%
“…A total of four genes, including AMH, PRLR, NOX1, and PGF, are screened as predicators of the prognostic model ( Figure 6 ). Of these, PRLR has been implicated in the pathology of breast and prostate cancer [ 46 , 47 ], NOX1 expression may be increased in prostate cancer with an important role in angiogenesis, cell growth, and tumor pathogenesis [ 48 , 49 ], and both AMH and PGF are reported as crucial genes in tumorigenesis [ 50 , 51 , 52 ]. Based on their potential biological roles and contributions in cancer, the developed immune-related prognostic model is sensitive and effective (AUC = 0.968, and the survival model is an independent prognostic factor), which would provide additional immune-based information for early risk appraisal and treatment management in prostate cancer.…”
Section: Discussionmentioning
confidence: 99%